1992
DOI: 10.1111/j.1365-3083.1992.tb02951.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against Secreted and Non‐Secreted Antigens in Mice after Infection with Live Mycobacterium tuberculosis

Abstract: Mice from four different inbred strains were infected with live Mycobacterium tuberculosis and the immune response to M. tuberculosis was followed for 24 weeks, using Western blotting. Nearly all mice, irrespective of H-2 type, reacted with the 38-kDa protein band. Antibodies against this secreted 38-kDa protein were the first to appear, 4 weeks after infection. Thereafter the secreted 19-kDa protein and non-secreted antigens, such as the 65-kDa and 33-kDa proteins, were recognized. The immune response against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…According to some papers (Drew et al, 2000;Verbon et al, 1992), secreted proteins may be more valuable in inducing specific immune response than non-secreted antigenic proteins. Results of western blot (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…According to some papers (Drew et al, 2000;Verbon et al, 1992), secreted proteins may be more valuable in inducing specific immune response than non-secreted antigenic proteins. Results of western blot (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Ag84 has been reported by some to be secreted (Verbon et al 1990), while others have concluded that it is not a secretory antigen Hermans et al 1995). It has been reported that mAb F126-2 and F126-5 recognize two different antigens of M. tuberculosis (Verbon et al 1990(Verbon et al , 1992: the former mAb recognizes a secreted 34-kDa protein and the latter a 33-kDa protein which is not secreted and which corresponds to the 36-kDa proline-rich antigen of M. leprae. TB33 appears to be a 33-kDa antigenic protein that is not secreted and is probably distinct from Ag84, but it bears the F126-2 epitope common to Ag84.…”
Section: Discussionmentioning
confidence: 99%
“…TB33 was recognized by mAb F67-1 and F126-5 that are known to react with a 33-kDa protein of M. tuberculosis (Verbon et al 1992). These two mAb recognize the linear sequence Tyr-Pro-Pro-Pro of the 36-kDa proline-rich antigen of M. leprae (Klatser et al 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that immunization with different antigens can preferentially or selectively induce either humoral immunity or CMI response (13). The 38-kDa antigen is known to be an immunodominant antigen during the development of the immune effector mechanism against tuberculosis (14,34). However, it is still not documented whether sensitization with this antigen evokes the Thl-or Th2-…”
Section: Discussionmentioning
confidence: 99%